Mapeamento do fluxo da informação entre sistemas para suporte a gestão de projetos - Rodrigo Abrantes Couy Baracho (2021)
The need for up to date, correct and available information for everyone involved in an engineering project is fundamental for its success. This research aims to analyze the interoperability between systems used in Project Management, mainly in relation to the information necessary for its management. Design Science Research was used with the steps of Problem Awareness, Artifact Development and Validation. This research is based on a literature review focused on the interoperability between systems and project management. Based on the author’s experience with project management in companies that supply equipment for mining and steel companies, and based on the findings of the literature review, a flowchart for mapping the flow of information between systems to support project management was elaborated. A questionnaire was sent to experts on the subject who, in addition to validating the proposal, pointed out suggestions for improvement. This research showed the relevance of the integration of information between systems to support in Project Management, pointing out necessary steps for its optimization, and supporting the development of an automatic integration between the systems.